Investigating accidents involving aircraft manufactured from polymer composite materials - Dunn, Leigh (Cranfield University, 2013)
This thesis looks into the examination of polymer composite wreckage from the perspective of the aircraft accident investigator. It develops an understanding of the process of wreckage examination as well as identifying the potential for visual and macroscopic interpretation of polymer composite aircraft wreckage. The in-field examination of aircraft wreckage, and subsequent interpretations of material failures, can be a significant part of an aircraft accident investigation. As the use of composite materials in aircraft construction increases, the understanding of how macroscopic failure characteristics of composite materials may aid the field investigator is becoming of increasing importance. The first phase of this research project was to explore how investigation practitioners conduct wreckage examinations. Four accident investigation case studies were examined. The analysis of the case studies provided a framework of the wreckage examination process. Subsequently, a literature survey was conducted to establish the current level of knowledge on the visual and macroscopic interpretation of polymer composite failures. Relevant literature was identified and a compendium of visual and macroscopic characteristics was created. Two full-scale polymer composite wing structures were loaded statically, in an upward bending direction, until each wing structure fractured and separated. The wing structures were subsequently examined for the existence of failure characteristics. The examination revealed that whilst characteristics were present, the fragmentation of the structure destroyed valuable evidence. A hypothetical accident scenario utilising the fractured wing structures was developed, which UK government accident investigators subsequently investigated. This provided refinement to the investigative framework and suggested further guidance on the interpretation of polymer composite failures by accident investigators.
Keywords: Fractography; Reconstruction; Failure Analysis; Fracture; Mishap